2022
DOI: 10.2147/idr.s371654
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Associated Risk Factors of Gram-Negative Bacterial Bloodstream Infections in Tikur Anbessa Specialized Hospital, Addis Ababa

Abstract: Background Bloodstream infections (BSIs) are significant causes of morbidity and mortality in Ethiopia and worldwide. Alarming is the rapid global spread of antimicrobial resistance (AMR) in bacteria. Objective To determine the microbial profile, antimicrobial susceptibility pattern, and associated risk factors for bloodstream infections in Tikur Anbessa Specialized Hospital (TASH) Addis Ababa Ethiopia. Methods A cross-sectional study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
(133 reference statements)
1
3
0
1
Order By: Relevance
“…The present study showed that ICU admission and exposure to invasive devices were risk indicators in acquiring infections with MDR K. pneumoniae strains, which is in agreement with several studies 3 , 4 , 8 , 32 . Furthermore, the increased risk of acquiring infections with MDR bacteria in the ICU is associated with the severity of the patient’s illness and underlying conditions, length of exposure to invasive procedures, extensive antibiotic use and increased patient contact with healthcare personnel and length of stay in the ICU 4 , 7 , 32 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study showed that ICU admission and exposure to invasive devices were risk indicators in acquiring infections with MDR K. pneumoniae strains, which is in agreement with several studies 3 , 4 , 8 , 32 . Furthermore, the increased risk of acquiring infections with MDR bacteria in the ICU is associated with the severity of the patient’s illness and underlying conditions, length of exposure to invasive procedures, extensive antibiotic use and increased patient contact with healthcare personnel and length of stay in the ICU 4 , 7 , 32 .…”
Section: Discussionsupporting
confidence: 93%
“…ICU admission has been documented as an independent risk factor for the acquisition of MDR K. pneumoniae by many authors 7 , 32 , 34 . It was suggested that ICU patients are at an increased risk of acquiring infections with MDR bacteria and most of which are associated with the use of invasive devices such as indwelling catheters and central venous catheters 4 , 7 , 31 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Et al [ 30 ] 0.20910977 0.0773275 0.34089205 Mekonnen et al [ 29 ] 0.14995179 0.09382511 0.20607847 Alebel et al [ 27 ] 0.14969699 0.09391756 0.20547643 Abdeta et al [ 40 ] 0.14658256 0.09069896 0.20246616 Alemayehu. Et al [ 38 ] 0.14505221 0.09029172 0.1998127 Mitiku et al [ 39 ] 0.14585564 0.09048406 0.2012272 Abda et al [ 26 ] 0.15089363 0.09481937 0.20696789 Bizuayehu et al [ 43 ] 0.15028805 0.09435938 0.20621672 Abayneh et al [ 37 ] 0.17417368 0.11178836 0.236559 Worku et al [ 33 ] 0.17417368 0.11178836 0.236559 Tilahun et al [ 32 ] 0.1223927 0.07197122 0.17281418 Beshah et al [ 41 ] 0.1467315 0.09193183 0.20153117 …”
Section: Resultsunclassified
“…Most of the bacteria 233 (54.2%) isolated were GNB. The detail of the bacteria identified and the antimicrobial susceptibility pattern of the isolates was described in our published article [ 37 ]. After excluding one Corynebacterium gleum and one Neisseria meningitidis , a total of 231(54.1%) GNB bacteria were further analyzed for determining their drug resistance mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of MDR, XDR, and PDR was indicated in our previous article [ 37 ]. The ICU department, neonate’s instrument usage during medical care, chronic illness, UTI, RTI, and history of incubation was the predominant factor for having the highest MDR GNB infection.…”
Section: Discussionmentioning
confidence: 99%